Separation incentives and minimum wages in a job-posting search framework - Amanda Gosling; Mathan Satchi (University of Kent, School of Economics, 2014)
We present a job posting model of a labour market where jobs differ in characteristics other than wages and workers differ in their marginal willingness to pay for such characteristics. This creates incentives for firms to separate workers by posting multiple jobs. The interaction between these separation incentives and the standard search frictions is the key contribution of the paper. The paper examines the implications for policies such as a minimum wage or ones which set minimum standards on these non-wage job characteristics. We show that policies that set standards on wages and the other job characteristics can increase the utility of the worst-off workers and may reduce inefficient forms of unemployment. Policies that only intervene in one aspect on the other hand may increase these forms of unemployment.
Keywords: J31; J32; J42; J64; J80; 330; Search; Job posting; Non-wage characteristics; Separation incentives; Minimum Wages